Classifying onset durations of early VLF events: Scattered field analysis and new insights. Issue 8 (4th August 2015) - Kotovsky, D. A.; Moore, R. C.
Abstract: The physical processes responsible for a variety of early VLF scattering events have not yet been satisfactorily identified. Properly categorizing the early VLF event type is imperative to understand the causative physical processes involved. In this paper, the onset durations of 26 exceptionally high signal‐to‐noise ratio early VLF scattering events are analyzed, using scattered fields to classify events. New observations of events that exhibit "slow" amplitude changes, but "fast" scattered field changes are presented, which call into question previous analyses of early/slow events. We separately identify and analyze three early VLF events that definitively exhibit slow scattered field behavior. Additionally, we identify a significant number of events which have onset durations between the current definitions of fast and slow. Four events are observed which unambiguously exhibit a rapid initial rotation of the scattered field phasor during the first few seconds of the recovery stage. Possible physical mechanisms are discussed. Key Points: VLF scattering Transient luminous events Ionospheric disturbances